Long- term outcome of paediatric patients with ANCA vasculitis - Pusey Charles D; Brogan Paul; Harper Lorraine; Smith Stuart W; Jawad Susan; Arulkumaran Nishkantha; Salama Alan D (BMC, 2011)
Abstract Background Primary systemic vasculitis presenting in childhood is an uncommon but serious condition. As these patients transfer to adult clinics for continuing care, defining long term outcomes with emphasis on disease and treatment- related morbidity and mortality is important. The aim of this study is to describe the long- term clinical course of paediatric patients with ANCA vasculitis. Methods The adult patients in our vasculitis clinics who had presented in childhood, with a follow up time of greater than 10 years were included. We also reviewed the literature for articles describing the clinical outcome of paediatric patients with ANCA vasculitis. Results We describe the clinical course of 8 adults who presented in childhood with ANCA vasculitis. 7 patients had Wegener's granulomatosis and 1 had microscopic polyangiitis. The median age at presentation was 11.5 years, and follow up time ranged form 11 to 30 years. Induction therapy for all patients was steroids and/or cyclophosphamide. Maintenance therapy was with azathioprine or mycophenolate mofetil. Biological agents were used in 3 patients for relapsed disease in adulthood only. Seven patients achieved complete remission. All patients experienced disease relapse, with a median of 4 episodes. Kidney function was generally well preserved, with median eGFR 76 ml/min. Only one patient developed end-stage renal failure and one patient died after 25 years of disease. Treatment-related morbidity rates were high; 7 suffered from infections, 4 were infertile, 2 had skeletal complications, and 1 developed malignancy. Conclusion Close long- term follow up of paediatric patients with ANCA vasculitis is imperative, as this patient cohort is likely to live long enough to develop significant treatment and disease- related morbidities. Prospective cohort studies with novel therapies including paediatric patients are crucial to help us determine the best approach to managing this complex group of patients. In addition, although not yet observed in our series, late cardiovascular morbidity remains a major longer-term potential concern for adult survivors of paediatric vasculitis.